THE EFFECT OF E-SERVICE QUALITY ON CUSTOMER SATISFACTION WITH COMPLAINT HANDLING AND CUSTOMER TRUST AS AN INTERVENING VARIABLE (Case Study at PT. PLN (Persero) UP3 Medan and North Medan, Medan City Working Area) - Ronald Sibuea; Endang Sulistya Rini; Rulianda Purnomo Wibowo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to test and analyze the effect of e-service quality on customer satisfaction with complaint handling and customer trust as intervening variables at PT. PLN (Persero) UP3 Medan and Medan Utara Medan City Working Area. The population of all users of the New PLN Mobile application at PT. PLN (Persero) UP3 Medan and Medan Utara Medan City Working Area totaling 3,256,389 users. The sample is 400 customers. The data analysis technique used is Partial Least Square (PLS). The results of the study indicate that e-service quality has an effect on customer satisfaction, e-service quality has an effect on complaint handling, e-service quality has an effect on customer trust, complaint handling mediates the effect of e-service quality on customer satisfaction, and customer trust mediates the effect of e-service quality on customer satisfaction.